Irrigation management : principles and practices - Burton, Martin (Wallingford, Oxfordshire ; Cambridge, Massachusetts : CABI, 2010)
A practical guide to improve efficiency and productivity in irrigated agriculture. It offers knowledge for the management of irrigation and drainage systems, including traditional technical areas of systems operation and maintenance, and expanding managerial, institutional and organizational aspects
1. Introduction -- 2. Components of irrigation and drainage systems -- 3. Management -- 4. Operation of the main system -- 5. Operation at the on-farm level -- 6. Maintenance -- 7. Training -- 8. Irrigation management transfer and organizational restructuring -- 9. Performance assessment, monitoring and evaluation
Includes bibliographical references and index
Keywords: Drainage -- Management; Irrigation -- Management